Implementasi E-Service pada Organisasi Publik di Bidang Pelayanan Pendidikan - Pratiwi, Yuliana (Jurnal Administrasi Publik, 2013)
The research was carried out of the demands of the information society that demands government to provide public services that fit their needs.To cope with the demand, the government adopted the use of information and communication technology called e-Government. PSB Real Time Online is a form of electronic services (e-Services) in the field of education in the city of Malang. This researchusesa qualitativemethod with focuses on the problem :Â  How is the implementation of e-Service in the PSB program Real Time Online? How the result of the implementation of e-Service program PSB Real Time Online in Good Governance perspective?.Results from the study showed that the implementation of the program PSB Real Time Online is successful in carrying out public services to adopt the application of information and communication technologies and realizing the principles of Good Governance especially transparency, efficiency, and simplicity.Sustained socializationto the communitythrough bothprint and electronic media has done before the implementation so that the implementation of Real Time Online PSB community understands the mechanisms that must be implemented ift hey follow the registration and data collectionat the school so there is no procedural error. Keywords : E-Service, Public Organization, Education services, PSB Real Time Online